S-band multiwavelength Brillouin Raman Fiber Laser - Ahmad, Harith; Zulkifli, Mohd Zamani; Norizan, Siti Fatimah; Jemangin, M.H.; Harun, Sulaiman Wadi (Elsevier, 2011)
In this paper we propose and demonstrate an S-band Brillouin–Raman Fiber Laser (BRFL). The S-band BRFL utilizes a Dispersion Compensating Fiber (DCF) as the non-linear gain medium in a linear cavity configuration and amplified by two 1425 nm, 380 mW pumped Raman Fiber Amplifiers (RFAs). A Brillouin Pump (BP) signal of 1515 nm at 12 dBm in power is injected into the setup to generate Stokes lines via the Stimulated Brillouin Scattering (SBS) process. The S-band BRFL is able of generating a Brillouin comb with 32 Stokes lines with a flat peak output power of −18 dBm. The best BP to Stokes power ratio of the system is determined to be 50:50, while a ratio of 70:30 is observed to generate Stokes with a higher peak power, but at the expense of the number of wavelengths. The S-band BRFL has many potential applications as multiwavelength sources for communications and sensors.